Heparins May Not Be the Optimal Anticoagulants for Sepsis and Sepsis-Associated Disseminated Intravascular Coagulation - Iba, Toshiaki; Helms, Julie; Totoki, Takaaki; Levy, Jerrold H. (Seminars in Thrombosis and Hemostasis, 2024)
Historically, heparin has had the longest historical use as an anticoagulant and continues this day to be the primary therapeutic option for preventing thrombosis and thromboembolism in critically ill hospitalized patients. Heparin is also used to treat sepsis and sepsis-associated disseminated intravascular coagulation (DIC) in various countries. However, the efficacy and safety of heparin for this indication remains controversial, as adequately powered randomized clinical studies have not demonstrated as yet a survival benefit in sepsis and sepsis-associated DIC, despite meta-analyses and propensity analyses reporting improved outcomes without increasing bleeding risk. Further, activated protein C and recombinant thrombomodulin showed greater improvements in outcomes compared with heparin, although these effects were inconclusive. In summary, further research is warranted, despite the ongoing clinical use of heparin for sepsis and sepsis-associated DIC. Based on Japanese guidelines, antithrombin or recombinant thrombomodulin may be a preferable choice if they are accessible.
Keywords: heparin; low-molecular-weight heparin; anticoagulants; sepsis; disseminated intravascular coagulation